2020
DOI: 10.1093/rheumatology/keaa605
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-release diclofenac conjugated to hyaluronate (diclofenac etalhyaluronate) for knee osteoarthritis: a randomized phase 2 study

Abstract: Objective To evaluate the efficacy and safety of diclofenac etalhyaluronate (DF-HA) (ONO-5704/SI-613), a novel DF-conjugated hyaluronate, in patients with knee OA in Japan. Methods In this randomized, double-blind, placebo-controlled phase 2 study, patients were randomly assigned (1:1) to receive either 30 mg of DF-HA or placebo intra-articularly at weeks 0, 4 and 8 and were followed up for 24 weeks. The primary outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
(14 reference statements)
2
14
0
Order By: Relevance
“…Similar to the primary outcome, most of the secondary outcomes indicated the superiority of 12 weeks of treatment with DF‐HA compared to placebo. These results confirmed the efficacy of DF‐HA and reproduced the results of our previous phase II study ( 18 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to the primary outcome, most of the secondary outcomes indicated the superiority of 12 weeks of treatment with DF‐HA compared to placebo. These results confirmed the efficacy of DF‐HA and reproduced the results of our previous phase II study ( 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy and safety of DF-HA in knee OA patients was confirmed in a previous trial (18), where DF-HA injected three times, once every 4 weeks for 12 weeks, showed statistically significant improvements in Western Ontario and McMaster University Osteoarthritis 3.1 Index (WOMAC) (19) pain subscores over placebo with no major safety concerns.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations